Konsultasi, Konseling Keluarga Berencana dan Kesehatan Reproduksi Berbasis Manajemen Keperawatan dalam Peningkatan Mutu Pelayanan Kesehatan Primer - Luh Putu Sukmayanti; Ni Ketut Devy Kaspirayanthi; Firdaus Indah Sari; Mery Angreani Safitri (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Family Planning (FP) and reproductive health consultation and counseling are essential strategies to improve adolescents’ knowledge, attitudes, and skills in preventing unintended pregnancy, sexually transmitted infections, and other reproductive health problems. This community service activity was conducted in Pupuan, Tabanan, on August 19th, 2025, using a nursing management–based approach in primary health care services, including planning, organizing, implementation, and evaluation of FP and reproductive health consultation and counseling for adolescents. The methods consisted of group health education, interactive discussions, and individual counseling delivered in structured service areas (registration and IEC desk, waiting area, private counseling room, interactive education room, and digital information booth) supported by presentation media, educational videos, and printed materials. The results showed an increase in adolescents’ knowledge and understanding regarding FP concepts, contraceptive methods, physical and psychosocial changes during adolescence, and the importance of maintaining reproductive health, as reflected in higher post-test scores and active participation during the sessions. Implementation of nursing management principles in service flow arrangement and nurses’ roles supported service quality, indicated by more orderly service flow, comfortable counseling atmosphere, and positive feedback on the clarity of information and the friendliness of providers. This program recommends strengthening and replicating FP and reproductive health consultation and counseling models based on nursing management in other primary health care centers as part of efforts to improve primary health care quality and achieve national FP and reproductive health targets.